ANALISIS EFEKTIVITAS PENGGUNAAN DANA DESA DI KAMPUNG KADUN JAYA DISTRIK WANIA KABUPATEN MIMIKA - PROVINSI PAPUA TENGAH - Fransina Helyanan; Adolfina Dolli Gujangge; Abu Bakar (ADMIN: Jurnal Administrasi Negara, 2023)
This study aims to determine the effectiveness of using village funds in Kampung Kadun Jaya, Wania District, Mimika Regency – Central Papua Province. The research method used in this research is descriptive method. The data used in this study are qualitative and quantitative data collected using observation and questionnaires. To measure the effectiveness of using village funds in Kampung Kadun Jaya, Wania District, Mimika Regency, Central Papua Province, the concept of respondent analysis was used, with development according to the objectives of this research. The results of this study indicate that the use of village funds in Kampung Kadun Jaya has been running effectively.